The eye speaks! decoding user experience through eye tracking of syntactical properties analysis for cultural artefact - M. I ., Siti Mastura; A., Sivaji; S. T., Soo; B., Rahmah; H., Hazreena; Ibrahim, Rahinah (American-Eurasian Network for Scientific Information, 2015)
Background: An artefact usage experience is able to provide a tremendous input on behavioural research. This paper presents about a computational methodology of eye tracking to lead designers and behavioural researchers to construct an effective procedure ensuring the excavation of user knowledge.